Paraitonion, the Ancient City and Harbor During the Graeco-Roman Period According to Ancient Sources - Moussa, Wessam Fekry Ibrahim (جامعة الإسكندرية - كلية السياحة والفنادق, 2020)
Marsa Matrouh today is well known as a tourist resort, but few historical facts are known about it. According to ancient sources, it once acted as a fishing village, and afterward a resupply harbor for ships trading in the Mediterranean. During early Egyptian times the area was known as Thehenu then,it was called Ammonia. During the Greco-Roman period it became Paraitonion or Paraetonium which are several forms of Bareton. It was of considerable importance in the Greco-Roman era because of its port, not easy to access, but fairly large and well protected. Strategically it was, like Pelousion in the east. The history of the city gained some global reputation when it was occupied by Marc Antony and Cleopatra. Justinian renewed and fortified it. Partial excavations have brought to light a Roman-era inscription with hints of work done in a public building, the remains of a church, of baths, and a statue of the Good Shepherd. Through the Byzantine period, the city is supposed to have considerable regional importance as it laid within the “Eparchy of Lower Libya” and was the seat of both the “Dux LimitisLibyci” and a “Christian bishop”. But prior to this era, classical sources about the history of the region are rare and flawed by their lack of clarity or the presence of some variations regarding the demographic and geographical characteristics of the area. So, this study aims to analyze and evaluate those sources in order to find out similarities or differences between them or to interpret a new image about the importance of the city and its ancient harbor and the role it once played during the Greco-Roman Era.
Keywords: بارايتونيون -- العصر الروماني -- مرسى مطروح، مصر